Arthroscopic management of comminuted fracture of the scapular glenoid secondary to electrical shock injury: a case report and literature review - Zhang, Zi; Meng, Binyang; Li, Wenhe; Wang, Qi; Cao, Jiangang (Frontiers in Surgery, 2025)
Arthroscopic management of scapular glenoid fractures caused by electrical injury represents an innovative approach for complex shoulder trauma involving both osseous and soft tissue damage. This technique uniquely combines the double-pulley system with a 3.0-mm double-suture anchor bridge fixation, allowing for smaller incisions and reduced surgical trauma. We report, for the first time, an arthroscopic case of comminuted anteroinferior glenoid fracture resulting from electrocution. A 53-year-old man presented with left shoulder dysfunction 8 days after electrical injury. CT and MRI revealed a comminuted glenoid fracture, a non-displaced greater tuberosity fracture, and a partial supraspinatus tear. Arthroscopic anchor fixation achieved anatomic reduction of the glenoid fragment without intraoperative complications, while the greater tuberosity fracture and rotator cuff injury were managed conservatively. At 15-month follow-up, the patient was pain-free (VAS score 0) with full shoulder function (Constant score 95, ASES score 94), and CT confirmed satisfactory glenohumeral congruency. This case demonstrates the technical feasibility of arthroscopic treatment for high-energy electrical shoulder trauma, with advantages of minimizing soft tissue disruption and reducing the risk of postoperative stiffness, though further studies are needed to validate long-term outcomes.